Aspectos psicológicos do uso patológico de internet - Fortim, Ivelise (2013)
The aim of this study was to understand the experience of Pathological Internet Use (PIU) from self-reported users who declare themselves as "internet addicts". This is qualitative research, being a documental, transversal and retrospective study. The data were treated in two approaches: (i) using a statistical program for text analysis; and (ii) using categories of analysis, which were then analyzed by Jungian Psychology. The survey was conducted with a sample of 189 subjects. A total of 278 messages sent by these subjects were collected in the period from 02/2001 until 06/2011. The results indicate that the most frequent use seems to be for communicating, for sexual purposes and for navigation. Men seem to feel more dependent on communication, sex and games, while women consider themselves more dependent on communication and relationships. Four presented more psychological aspects can be highlighted. The first aspect is relative to the control: the internet gives the user a sense of great control over relationships with others and the image of itself. The second is that PIU appears to be a process of coping with situations of stress and anxiety. The pleasure obtained by some Internet activities shown to be additive, which means that life is restricted to the computer; pleasure seems to be coming from the control of activities, the ability to escape that they can provide, the ease and availability of sexual material, the infinitude of information and people. The third is related to the characteristic of the internet being seen at the same time as illusory as real, which enable a "half real" relationship with other. The forth is that many individuals are using the internet because it seems to liberate shadow aspects, sexual behavior, aggressive and also another aspects which are known but not assumed to others (as in shyness), the Internet seems give the user the feeling that he can be free, can be whoever he wants without censorship or social sanctions. Many users report negative consequences, such as negatively impact at studies, work, family and marital conflicts, social impairment, carelessness with themselves and with children. It is concluded that the internet is not harmful itself, but may provide a pathological use with serious consequences for certain users who are in vulnerable situations and use the internet to alleviate problems